The relationship between otolith size and estimated age of tigertooth croaker (Otolithes ruber Bloch and Schneider, 1801) in Oman Sea, Iran. (5th June 2017) - Rahnama, B.; Kamrani, E.; Radfar, F.; Yadollahvandmiandoab, R.; Parsa, M.
Summary: The relationships between somatic growth and otolith dimensions, otolith size to estimated age and growth parameters of the tigertooth croaker ( Otolithes ruber ) were investigated in 100 specimens (size range: 19.1–52.0 cm, total length) from the Oman Sea area, September 2014. All 100 otoliths were sectioned and determined by age. The oldest specimen was a 4.5‐year‐old female with a total length of 40.6 cm; the youngest specimen was also a female estimated at 1 year of age with a total length of 19.1 cm. The von Bertalanffy growth equation was estimated as L t = 54.70 (1 − exp (−0.37 ( t + 0.21))). Concluded was that there is a significant relationship between body size, otolith dimensions and estimated age of Otolithes ruber .